Effect of daily use of Lavender (Lavandula angustifolia) and Cedarwood (Cedrus atlantica) essential oils on nocturnal anxiety and respiratory disorders: a case report - Silva, Rosimeire Barbosa da; Carmago, Janaina de Oliveira Barros e Silva; Ribeiro, Giselle dos Santos; Silva, Francisco Rafael Oliveira da (Brazilian Journal of Case Reports, 2023)
Aromatherapy is a healing practice that has been used for centuries to promote physical and psychological wellbeing. The practice involves the use of essential oils (EOs) extracted from plants to treat a variety of conditions. Aromatherapy is believed to work by stimulating the sense of smell and the limbic system of the brain, which is responsible for emotions, memories, and learning. Lavender (Lavandula angustifolia) is a safe essential oil with well-established sedative and hypnotic properties Additionally, the properties of essential oils obtained from different species of Cedrus, such as C. atlantica, have been reported for their use in aromatherapy to obtain many clinical benefits traditionally attributed to the genitourinary, musculoskeletal, and cutaneous systems. However, the role of essential oil in the treatment of nocturnal anxiety and respiratory disorders in sleep is unclear, which makes clinical studies necessary to reinforce this hypothesis. Here, we present a clinical case of an adult patient with daily anxiety attacks and nocturnal breathing disorders effectively treated with the inhaled use of essential oil of Lavender (Lavandula angustifolia) and Cedarwood (Cedrus atlantica).